Biomimetic platelet nanoparticles encapsulated with proteasome inhibitor bortezomib for multiple myeloma treatment - Guangtao Gao; Yong Xu; Jingjing Gan; Xinya Cao; Xiaoqing Dong; Mengkun Fang; Ying Du; Peipei Xu; Junyi Che; Bing Chen (APL Materials, 2023)
The discovery of bortezomib (BTZ) has been a major clinical breakthrough for multiple myeloma (MM) treatment. However, its clinical application is restricted to a low tumor-targeting ability, fast clearance, and treatment-related toxicity. Here, we report a targeting strategy of MM by poly(lactic-co-glycolic acid)(PLGA) nanoparticles cloaking with platelet membranes (PMs) encapsulating BTZ (PM/BTZNPs). The drug delivery system could encapsulate sufficient BTZ with suitable nanoparticle characteristics for cellular uptake via an easy fabrication process. Of note, PM coating markedly enhances the selectivity, cellular uptake, and anticancer effects of BTZ in LP-1 cells. PM/BTZNPs further display a targeted drug delivery system to MM, causing a low toxicity effect and exhibiting an obvious survival advantage compared to nontargeted BTZ. Therefore, PM/BTZNPs, as a biomimetic nanotherapeutic formulation, demonstrate a high potential for MM patients.